Prevalence, Clinical Manifestations, and Biochemical Data of Hypertensive versus Normotensive Symptomatic Patients with COVID-19: A Comparative Study: Running title: Hypertension and COVID-19 - De Sanctis, Vincenzo (Acta Biomedica Atenei Parmensis, 2020)
Background: There is a scarcity of data regarding the effect of hypertension on the clinical presentation and outcome of symptomatic patients with COVID-19 infection in comparison with non-hypertensive patients. Aim of the study: To describe the clinical presentation, radiological and hematological data of a cohort of symptomatic COVID-19 positive hypertensive patients (n=50) in comparison with another cohort of normotensive symptomatic COVID-19 positive patients (n=250) diagnosed at the same time and managed in the same health facilities (from Jan 2020 to May 2020). Associated comorbidities were assessed, and the Charlson Comorbidity Index was calculated. The outcomes, including duration of hospitalization, length of ICU stay, duration of mechanical ventilation, and duration of O2 supplementation, were also assessed. Results: The prevalence of hypertension in symptomatic COVID-19 positive patients was 50/300 (16%; the prevalence of hypertension in Qatari adults is ~30%). Hypertensive patients had a higher prevalence of DM, CKD, and cardiac dysfunction compared to normotensive patients (p